2001
DOI: 10.2320/jinstmet1952.65.11_972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Residual Stress on Lattice Parameter and Hardness of Titanium Nitride Films Deposited by Reactive HCD Ion Plating

Abstract: Residual stress produced in titanium nitride films deposited onto substrates of high speed steel, SKH51, was studied by using sin 2 c method as a function of process parameters: deposition temperature, deposition time, electron beam current, substrate bias voltage, distance from an evaporation source to a substrate, tilt angle of a substrate axis, total gas pressure, and gas mixture ratioMeasurements showed that compressive stress occurred in the films except one deposited without any applied bias voltage to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Conditions for residual stress measurement were proposed previously. 11) We confirmed that all films were of single phase TiN.…”
Section: Characterization Of Tin Filmssupporting
confidence: 69%
See 2 more Smart Citations
“…Conditions for residual stress measurement were proposed previously. 11) We confirmed that all films were of single phase TiN.…”
Section: Characterization Of Tin Filmssupporting
confidence: 69%
“…However, it is considered that relaxation of stress occurs because of formation of many open pores by worsened adhesion of films in the range of lower substrate temperature. 11,21) Figure 14 shows the relationship between critical passivation current density i crit and compressive stress for two series of deposition temperatures T I and substrate bias voltages V B . Except for the 0 V-coated substrate, critical passivation current density i crit becomes higher with higher compressive stress: in other words, films of higher compressive stress have many open pores, which cause lower protective quality.…”
Section: Effect Of Compressive Stress On Open Pore Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…applied to the substrate, active particles, N ions and Ar ions don't collide with the synthesized film, and therefore, there is no compressive residual stress to be applied to the film and the hardness of the film is considered to be low. On the other hand, when a substrate bias is applied, since active particles, N ions and Ar ions are strongly attracted, compressive residual stress is generated and hardness is considered to increased [21,22]. Fig.…”
Section: Film Thickness and Film Hardnessmentioning
confidence: 99%